Accurate identification of layer number for few-layer WS2 and WSe2 via spectroscopic study. (7th February 2018) - Li, Yuanzheng; Li, Xinshu; Yu, Tong; Yang, Guochun; Chen, Heyu; Zhang, Cen; Feng, Qiushi; Ma, Jiangang; Liu, Weizhen; Xu, Haiyang; Liu, Yichun; Liu, Xinfeng
Abstract: Transition metal dichalcogenides (TMDs) with a typical layered structure are highly sensitive to their layer number in optical and electronic properties. Seeking a simple and effective method for layer number identification is very important to low-dimensional TMD samples. Herein, a rapid and accurate layer number identification of few-layer WS2 and WSe2 is proposed via locking their photoluminescence (PL) peak-positions. As the layer number of WS2 /WSe2 increases, it is found that indirect transition emission is more thickness-sensitive than direct transition emission, and the PL peak-position differences between the indirect and direct transitions can be regarded as fingerprints to identify their layer number. Theoretical calculation confirms that the notable thickness-sensitivity of indirect transition derives from the variations of electron density of states of W atom d-orbitals and chalcogen atom p-orbitals. Besides, the PL peak-position differences between the indirect and direct transitions are almost independent of different insulating substrates. This work not only proposes a new method for layer number identification via PL studies, but also provides a valuable insight into the thickness-dependent optical and electronic properties of W-based TMDs.